Analisis input – output: Dampak sektor pertanian terhadap perekonomian, pendapatan rumah tangga, dan kesesempatan kerja - Azhari, Wahid Fahmiza; Purnomo, Didit (Nur Science Institute, 2022)
Development is a condition desired by every region or region. Development can come from any sector in the area. The agricultural sector is still the leading sector in the economy and is a sector that is relied upon in the source of income for the provision of jobs compared to other sectors. This makes the agricultural sector a very influential sector in the economy in Indonesia. This article was created with the aim of knowing how the agricultural sector is related to other sectors in Indonesia. The analysis used in this research is input-output analysis, using secondary data from the Indonesian Input-Output Table in 2010. The results of the study indicate that the addition to the agricultural sector has a positive impact in the form of additions to the sector itself and other sectors both in terms of sectoral output, household income, and employment opportunities.